The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/acn3.538
|View full text |Cite
|
Sign up to set email alerts
|

CSF/serum matrix metallopeptidase‐9 ratio discriminates neuro Behçet from multiple sclerosis

Abstract: In neuro Behçet disease with multiple sclerosis‐like features, diagnosis could be challenging. Here, we studied the cerebrospinal fluid and serum inflammatory profile of 11 neuro Behçet and 21 relapsing‐remitting multiple sclerosis patients. Between the soluble factors analyzed (MMP9, TNF α, IL6, CXCL13, CXCL10, CXCL8, IFN γ, IL10, IL17, IL23, and others) we found MMP9 increased in neuro Behçet serum compared to multiple sclerosis and decreased in cerebrospinal fluid. Furthermore, neuro Behçet analysis of circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[203][204][205] In the progressive disease course, when other CSF variables may be normal, the IL-6 concentration is raised, 50 206 although less raised than in acute attacks. 207 In one study, CXCL10 concentrations were higher than in samples from controls and patients with multiple sclerosis, 206 but not in another, 208 and IL-10 concentrations were the same in one study but not another. 207 209 B cell activating factor concentrations are higher in the CSF in those with progressive neurological Behçet's syndrome than those with acute episodes.…”
Section: Cerebrospinal Fluidmentioning
confidence: 89%
“…[203][204][205] In the progressive disease course, when other CSF variables may be normal, the IL-6 concentration is raised, 50 206 although less raised than in acute attacks. 207 In one study, CXCL10 concentrations were higher than in samples from controls and patients with multiple sclerosis, 206 but not in another, 208 and IL-10 concentrations were the same in one study but not another. 207 209 B cell activating factor concentrations are higher in the CSF in those with progressive neurological Behçet's syndrome than those with acute episodes.…”
Section: Cerebrospinal Fluidmentioning
confidence: 89%
“…Although less sensitive, CXCL13 CSF concentration showed very high specificity (60.0% sensitivity and 93.3% specificity). Several studies have also explored CSF CXCL13 expression in MS patients showing higher levels than in healthy controls or in patients with other inflammatory neurological diseases [36,37]. Furthermore, CXCL10 levels were higher in both RMS and PMS compared to non-inflammatory controls and CXCL8 levels in PMS compared to both control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors showed significant elevation of CSF IL-6 in patients with progressive NBD compared to patients with active BD without neurological manifestations [ 24 ]. Moreover, it was noted that CSF, but not serum samples of NBD patients with acute parenchymal NBD, displayed significantly increased IL-6 levels, as compared to other groups [ 40 ]. Wang, et al, showed that the IL-6 level, which was higher in CSF of NBD patients, dropped when the disease activity subsided [ 16 ].…”
Section: Discussionmentioning
confidence: 99%